(untitled) (Altre Modernità, 2019)
This essay outlines the importance of Donne’s Anatomie of the World (1611), showing its relevance as a document of an age of transition, an age in which the ancient world literally died and the horizon of the new philosophy brought about a completely different conception of and relation to Nature. But the Anatomie is much moreit is the celebration of the power of poetry, of the everlasting Word, which alone can remember the broken fragments of the world and recreate it through its visions of unity and meaning.